Agrobacterium tumefaciens-mediated transformation of Paracoccidioides brasiliensis (2004)
ABSTRACT: Paracoccidioides brasiliensis is the causative agent of paracoccidioidomycosis, an important mycosis endemic to Latin America. As the tools to study gene function in P. brasiliensis are only in the early stage of development, there is presently no system that allows for both the delivery and integration of exogenous nucleic acids into its genome. We report in this paper the transformation of the yeast phase of P. brasiliensis (ATCC-60855) with Agrobacterium tumefaciens (GV3101) carrying the vector pAD1625. The microorganisms were co-cultivated for 2 days and then incubated for 10 days at 358C on selective media. PCR and dot-blot targeted at a fragment of 222 bp from the hph (hygromycin phosphotransferase) gene which confers Hygr confirmed the transformation of P. brasiliensis.